Alopecia and Periodontitis: Exploring the connecting dots - Jaya Agrawal; Nand Lal; Rameshwari Singhal (Wolters Kluwer Medknow Publications, 2023)
Alopecia areata is a systemic disease with nonscarring hair loss from the scalp, face, or any part of the body. The disease with undetermined etiology and pathogenesis has a considerable impact on the social life of patients which gradually builds up stress and expedites further deterioration of their condition. Interestingly, in such patients, besides stress-relieving exercises and immunomodulators, well-timed dental assessment and prompt treatment have contributed to improving the prognosis of alopecia. This depicts an interrelationship between alopecia and oral foci of infections. Over the past few decades, periodontitis has remained to be one of the predominant forms of oral focus of infection for systemic diseases. The present review throws light on the role of stress and autoimmunity in establishing a possible correlation between alopecia and periodontitis. It is augmented with documented case reports, demanding a complete oral examination in patients with the unexplained origin of alopecia. An interdisciplinary approach is the need of the hour which can prevent the progression of both the diseases as well as other oral infections.